Health Care Decisions as a Family Matter: Intrahousehold Education Externalities and the Utilization of Health Services - Lindelöw, Magnus (World Bank, Washington, D.C., 2013)
The author is concerned with the role of education as a determinant of health care choices. His central premise is that utilization of health services is determined not solely by an individual's own education, but rather by a notion of effective education, which incorporates the educational attainment of other household members. The author sets out a general framework for representing intra-household education externalities, and proposes a number of specific hypotheses concerning the way in which the education of different household members affects health care choices. He tests these hypotheses on data from Mozambique, focusing on maternity services and child immunizations. The author draws five major conclusions from the analysis. First, while maternal education seems to be the education variable of primary importance for the health care choices under consideration, the education of other household members has a significant and sometimes large effect. Second, his analysis suggests that while the education of the person (non-spouse) in the household with the highest-level education is important, the level of education of additional household members does not have an impact on health care choices. Third, the data provide no evidence of a gender difference in education externalities. Fourth, the author examines the merits of two alternative representations of the education externality, but is unable to conclude unambiguously in favor of one specification over the other. Finally, although the analysis highlights the importance of both education and a number of other explanatory variables in understanding health care choices, spatial fixed effects remain highly significant.